Effect of weight loss on coronary circulation and adiponectin levels in obese women - Coppola, Antonino; Marfella, Raffaele; Coppola, Ludovico; Tagliamonte, Ercole; Fontana, Dario; Liguori, Erminio; Cirillo, Teresa; Cafiero, Maria; Natale, Silvana; Astarita, Costantino (International journal of cardiology, 2009)
Obesity is independently associated with coronary endothelial dysfunction. Adiponectin, a protein whose circulating levels are decreased in obesity, has direct effects on vascular function. The aim of this study was to investigate in obese women the effect of sustained weight loss on coronary circulation and circulating adiponectin levels. Coronary flow velocity reserve (CFVR), assessed by transthoracic Doppler echocardiography (TTDE), blood pressure, lipid, glucose and insulin, HOMA scores, CRP-protein (CRP), and adiponectin parameters were investigated in forty obese pre-menopausal women and 40 healthy matched normal weight women at baseline and after sustained weight loss. At baseline, the obese group had significantly higher fasting glucose ( P < 0.05), insulin concentrations ( P < 0.01), HOMA scores ( P < 0.001), C-reactive protein (CRP) levels ( P < 0.001) and lower plasma adiponectin levels ( P < 0.001) than the controls. CFVR was significantly lower in obese group than in the normal weight group ( P < 0.05). After 12 months of a multidisciplinary program of weight reduction, obese women lost at least 10% of their original weight. Fasting glucose (< 0.001) and insulin concentrations ( P < 0.001), HOMA scores ( P < 0.001), CRP levels ( P < 0.01) were significant reduced, whereas adiponectin levels ( P < 0.001) and HDL cholesterol ( P < 0.05) showed a significant increment. CFVR value significantly improved in obese subjects ( P < 0.001). There was a significant correlation between changes in CFVR and changes in adiponectin levels ( r = 0.47, P < 0.05). Multivariate analysis showed that adiponectin was the only independent predictor of change in CFVR ( r = 0.38, P < 0.05). In obese women the weight loss improves coronary circulation and increases adiponectin levels. The improvement in coronary circulation is associated with adiponectin levels.